PRELIMINARY HYDROBIOLOGICAL STUDIES ON THE KANASGERI BACKWATERS - Telang, K Y; Jose, M M; Nandakumar, G (Indian Journal of Fisheries, 2011)
Preliminary hydrobiological in’t^stigaitions of the Kanasgeri backwater area ; adjacent to the Kali estuary in Noitfi rKanarft carried out during September 1976- August 1977 revealed that the area’could be utilised for aquacUlture purposes